Bioluminaire. - Lim, Daniel Yu-Heng. (2010)
Bioluminiaire, Creating Possibilities and Appreciation for the Natural world. The mystifying glow emitted by Bioluminescent life- forms can never explain its own allure. Drawn from nature, the poetic quality of light exuded is awe inspiring and calming. This project revolves around the intrigue achieved from these life-forms, and curious experimentation to re-create the mystic, bringing the magic into the home.